Fission yeast Rhp51 is required for the maintenance of telomere structure in the absence of the Ku heterodimer - Kibe, Tatsuya (Oxford University Press, 2003)
The Schizosaccharomyces pombe Ku70–Ku80 heterodimer is required for telomere length regulation. Lack of pku70(+) results in telomere shortening and striking rearrangements of telomere-associated sequences. We found that the rearrangements of telomere-associated sequences in pku80(+) mutants are Rhp51 dependent, but not Rad50 dependent. Rhp51 bound to telomere ends when the Ku heterodimer was not present at telomere ends. We also found that the single-stranded G-rich tails increased in S phase in wild-type strains, while deletion of pku70(+) increased the single-stranded overhang in both G(2) and S phase. Based on these observations, we propose that Rhp51 binds to the G-rich overhang and promotes homologous pairing between two different telomere ends in the absence of Ku heterodimer. Moreover, pku80 rhp51 double mutants showed a significantly reduced telomere hybridization signal. Our results suggest that, although Ku heterodimer sequesters Rhp51 from telomere ends to inhibit homologous recombination activity, Rhp51 plays important roles for the maintenance of telomere ends in the absence of the Ku heterodimer.